2022
DOI: 10.1021/acsomega.2c00068
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Nanocomposite Pour Point Depressant on Wax Deposition in Different Flow Patterns from the Perspective of Crystallization Kinetics

Abstract: Wax deposition is one of the core issues affecting flow assurance studies of crude oil pipelines, particularly with deep and ultradeep water conditions. Nanocomposite pour point depressants (NPPDs) provide a novel and effective strategy for inhibiting wax deposition and have recently attracted increasing research attention. Although recent advances have been made in understanding the performance and mechanism of NPPDs, the effect of flow pattern remains an open question. In this paper, deposition thicknesses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…For details on the experimental devices, we suggest the readers to refer to our previous articles. 30 …”
Section: Methodsmentioning
confidence: 99%
“…For details on the experimental devices, we suggest the readers to refer to our previous articles. 30 …”
Section: Methodsmentioning
confidence: 99%
“…Wang et al 101 delved into the wax inhibition mechanism of nanocomposite pour point depressants under laminar and turbulent flow regimes. They highlighted the enhancement of wax crystal morphology and the reduction in wax crystal numbers were key factors contributing to the decreased wax deposition rate (see Figure 19).…”
Section: Controversial Mechanism Of Improving the Wax Deposition Char...mentioning
confidence: 99%
“…Wax inhibition mechanism of nanocomposite pour point depressants under different flow states. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Influencing Factors Of Wax Depositionmentioning
confidence: 99%
“…Many scholars have interpreted the macroscopic rheology from the perspective of micromechanisms of waxy crude oil in order to find the core factors affecting the gelling of waxy crude oil. These studies focus on the rheological properties of waxy crude oil, such as gel point, viscosity and viscosity–temperature properties, thixotropy, and yield properties. The complex mechanical properties of waxy crude oil systems have been enriched by exploring the gelling process and law of waxy crude oil with small amplitude oscillatory shear experiment and the destruction process of gelling structure under large amplitude oscillatory shear. At the microscopic level, many studies focus on the microscopic morphology of wax crystals and try to describe the microscopic morphology of wax crystals and their aggregates by polarizing microscopy, electron microscopy, confocal microscopy, , X-ray diffraction, , and computerized tomography (CT) scanning techniques. , In addition, stereology and fractal geometry theory were used as guides to characterize the microscopic morphological characteristics of wax crystals quantitatively. Further, the quantitative relationship between wax crystals and the macroscopic rheological properties of waxy crude oil was constructed to explain the rheological and gelling properties. Although the research on the rheological mechanism of waxy crude oil has made continuous progress, in recent years, with the deepening of research work, some scholars have found that there is insufficient evidence to explain the complex rheological properties and gelling mechanism of waxy crude oil solely based on the morphological changes of wax crystals .…”
Section: Introductionmentioning
confidence: 99%